Nutrient composition and mycotoxin contamination of commercially sold premixed cereals for complementary feeding of infants in Malawi: Test results for 94 samples of 8 brands (P11-079-19) - Gilbert, Rachel; Subedi, Binita; Wallingford, Jessica; Wilson, Norbert; Masters, William A. (Oxford University Press, 2019)
High quality fortified premixed cereals can help caregivers meet infants’ nutrient needs after 6 months of exclusive breastfeeding, as complementary foods alongside breastmilk especially where family foods have low nutrient density. Such cereals are widely used in nutrition assistance programs, but commercially-sold brands are rarely subject to quality assurance using international standards for composition and labeling. Previous work found low and variable nutrients and high mycotoxin levels in a few samples. This study aimed to provide the first combined test for nutrient and mycotoxins in multiple samples of all premixed cereal brands for sale in a country, using Malawi as an example of a country with high burdens of child malnutrition and an active market for commercial premixed cereals.